Peripheral neuropathy in non-Hodgkin's lymphoma patients receiving vincristine with and without aprepitant/fosaprepitant - Edwards, Jessi K; Bossaer, John B; Lewis, Paul O; Sant, Ashley (Journal of oncology pharmacy practice, 2020)
Peripheral neuropathy is a common treatment-related adverse effect associated with vincristine. Vincristine is a major CYP3A4 substrate and is often administered alongside the neurokinin-1 (NK-1) receptor antagonists, aprepitant or fosaprepitant, which are moderate CYP3A4 inhibitors. This inhibition may result in increased concentrations of vincristine and an increased incidence of toxicity. The primary objective of this study was to investigate if there is a clinically significant drug interaction between vincristine and aprepitant or fosaprepitant resulting in early-onset peripheral neuropathy. The secondary objective of this study was to investigate the cumulative rate of chemotherapy-induced peripheral neuropathy (CIPN). This was a single-centered, retrospective, cohort chart review. Patients receiving vincristine-based chemotherapy between 1 July 2010 through 30 June 2018 were identified and reviewed for concomitant use of aprepitant or fosaprepitant and incidence of neuropathy. Early-onset CIPN was defined as neuropathy onset during the first cycle of chemotherapy. A total of 115 subjects were retrospectively reviewed over the study period, of whom 71 were included in the aprepitant/fosaprepitant group and 44 were included in the group without a NK-1 receptor antagonist. Of the subjects who received aprepitant/fosaprepitant, 26.7% experienced early-onset peripheral neuropathy as compared to 22.7% in the group without a NK-1 receptor antagonist ( = 0.627). Overall, CIPN was higher in the group who received aprepitant/fosaprepitant compared to the group without (56% vs. 36%, = 0.036). There appears to be an increased risk of CIPN with the concomitant use of vincristine and aprepitant or fosaprepitant.